2012
DOI: 10.1002/app.36427
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties and melt strength of LDPE during coextrusion process

Abstract: Rheological properties and mechanical strength of coextruded low‐density polyethyelene (LDPE) were studied in this work. The influences of die temperature, shear rate at skin and core layers, and number of extrusion passes at the core layer were of interest. The experimental results suggested that the viscosity and swelling behavior of LDPE coextrudate were more dependent on the shear rate of skin layer as compared with that of core layer. Increasing die temperature resulted in decreases in viscosity and die s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…20 Frequency functions in shear and elongational rheology are the two main methods to characterize viscoelasticity. 21,22 Strain-hardening behavior in elongational flow is an important component of viscoelasticity. Thus, in the previous work, the tensilehardening behaviors of polymers were used to describe the melt foamability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Frequency functions in shear and elongational rheology are the two main methods to characterize viscoelasticity. 21,22 Strain-hardening behavior in elongational flow is an important component of viscoelasticity. Thus, in the previous work, the tensilehardening behaviors of polymers were used to describe the melt foamability.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work has demonstrated that the polymer foamability is closely related to its viscoelasticity . Frequency functions in shear and elongational rheology are the two main methods to characterize viscoelasticity. , Strain-hardening behavior in elongational flow is an important component of viscoelasticity. Thus, in the previous work, the tensile-hardening behaviors of polymers were used to describe the melt foamability. This hypothesis assumes that the apparent tensile-hardening behavior prevents the bubbles from cracking and thus corresponds to good foamability.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizing additives, such as peroxides, can enhance the tetra‐ and tri‐functional branches in the polyethylene chains 24 and crosslinks 25 . On the other hand, low‐density polyethylene (LDPE) is already a highly branched polymer, so the extrusion process can result in further branching or crosslinking reactions generating more end groups and decreasing the mechanical properties 7,26–29 . Radical attacks can increase the scission rate in an oxidative environment, 30,31 while macroradicals can lead to higher branching reaction in inert or reducing environments 15,32–34 …”
Section: Introductionmentioning
confidence: 99%
“…25 On the other hand, low-density polyethylene (LDPE) is already a highly branched polymer, so the extrusion process can result in further branching or crosslinking reactions generating more end groups and decreasing the mechanical properties. 7,[26][27][28][29] Radical attacks can increase the scission rate in an oxidative environment, 30,31 while macroradicals can lead to higher branching reaction in inert or reducing environments. 15,[32][33][34] A high amount of research was performed on the mechanical degradation of recycled polymers such as PE with similar physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, most studies concerning layer interface deformation concentrate on traditional coextrusion processing, which shows relatively simple flow behavior . Experimental and numerical analysis methods were widely used to study these problems in the first 20 years of development; however, these methods were gradually replaced by the finite element method (FEM), which is a powerful tool for easily and quickly studying the rheology of polymer melts in a mold.…”
Section: Introductionmentioning
confidence: 99%